PENGARUH INSTAGRAM TERHADAP KETERLIBATAN ORANG MUDA KATOLIK DALAM HIDUP MENGGEREJA DI PAROKI SANTO PIUS X BLORA - Lestari, Lusiana Dewi; Gaudiawan, Antonius Virdei Eresto (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2020)
Instagram is one of the prominent social media, even among the OMK (Youth Catholic Organization) that gives many advantages. The advantage was used for accumulating a community by instagram account in a Parish. This research has to analyze the impact of instagram, toward OMK’s involvement in the Church; instagram and social media; the use of instagram account of young Catholic parish of Saint Pius X Blora; and the impact of the instagram account of Saint Pius X Blora’s parish for the youth involvement in the life of the Church. This study used quantitative method with Google Form service. The respondents was consist of 70 young people of Saint Pius X parish in Blora. The conclusions of the research are Instagram was a social media which displayed images or videos as their content. The OMK parish of Saint Pius X Blora has an account called “omkpius10”. The content was uploaded is OMK’s mutual activities, spiritual activities, Liturgy services, and Christian songs arrangement. OMK’s instagram account has the positive impact of inspiring the OMK to become more actively involved, strengthened closeness, and attracting OMK who has been less active to be more active in the Church activity.